Psychosocial influences upon young men and adolescent males to comply with messages of safe sexual behaviour - Slee-Sellars, Amy (2012)
This critical review examined the literature to explore the psychosocial influences upon young men and adolescents males to comply with messages of safer sexual behaviour. Young males aged between 15-24 years are at-risk of contracting an STI despite extensive health promotion efforts to reduce this. The rate of STIs within this group increases each year, indicating that there are sexual health needs of this population that are not being provided for. It is important to examine literature in this area in order to ensure that health professionals who come into contact with young males for sexual health purposes are able to understand how their individual circumstances may impede their ability to comply with messages of safe sex. By understanding this further, interventions and advice can be more appropriate to an individual and enable them to engage with messages of safe sexual behaviour. The examination of the literature identified three key themes that are able to influence an individual’s sexual attitudes and behaviours. The variables within each theme are discussed and their potential interactions are explored.